3D printing of amorphous solid dispersions: A comparison of fused deposition modeling and drop-on-powder printing - Nadine Gottschalk; Malte Bogdahn; Julian Quodbach (Elsevier, 2023)
Nowadays, a high number of pipeline drugs are poorly soluble and require solubility enhancement by e.g., manufacturing of amorphous solid dispersion. Pharmaceutical 3D printing has great potential in producing amorphous solid oral dosage forms. However, 3D printing techniques differ greatly in terms of processing as well as tablet properties. In this study, an amorphous formulation, which had been printed via Fused Deposition Modeling and drop-on-powder printing, also known as binder jetting, was characterized in terms of solid-state properties and physical stability. Solid state assessment was performed by differential scanning calorimetry, powder X-ray diffraction and polarized microscopy. The supersaturation performance of the amorphous solid dispersion was assessed via non-sink dissolution. We further evaluated both 3D printing techniques regarding their processability as well as tablet uniformity in terms of dimension, mass and content. Challenges and limitations of each 3D printing technique were discussed. Both techniques are feasible for the production of amorphous formulations. Results indicated that Fused Deposition Modeling is better suited for production, as the recrystallization tendency was lower. Still, filament production and printing presented a major challenge. Drop-on-powder printing can be a viable alternative for the production of amorphous tablets, when a formulation is not printable by Fused Deposition Modeling.